2012
DOI: 10.1016/j.sbspro.2012.12.223
|View full text |Cite
|
Sign up to set email alerts
|

Future Research Centers: The Place of Creativity and Innovation

Abstract: Progressive research activities, as essential factors in future societies, are strongly dependent on the creativity and innovation. The built environment is considered as one of the influential aspect in creativity and innovation and its appropriate features are sought here. Among various choices, academic research centers of architecture and urban design are adopted for the sake of this study. Four effective spatial characteristics are first identified as influential spatial characteristics in this case, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The diversity of spaces referred to having different furniture for different activities and spaces to work in the office: a desk, a sofa and a hammock. Bisadi et al (2012) also found that designed common spaces were perceived to increase creativity: Connectedness and the continuity of open and closed spaces were found to enhance visibility and the sense of proximity. Furthermore, they recommend designing special places for 'gathering, chatting, playing and exercising' (Bisadi et al, 2012: 241).…”
Section: Group 3: Studies Examining Specifically Designed Spaces For mentioning
confidence: 94%
See 2 more Smart Citations
“…The diversity of spaces referred to having different furniture for different activities and spaces to work in the office: a desk, a sofa and a hammock. Bisadi et al (2012) also found that designed common spaces were perceived to increase creativity: Connectedness and the continuity of open and closed spaces were found to enhance visibility and the sense of proximity. Furthermore, they recommend designing special places for 'gathering, chatting, playing and exercising' (Bisadi et al, 2012: 241).…”
Section: Group 3: Studies Examining Specifically Designed Spaces For mentioning
confidence: 94%
“…The author is cautious about drawing any consistent conclusions on the relationship between designing spaces for creativity and calls for more research. Bisadi et al (2012) studied how architecture and urban design researchers would build an academic research centre while being aware that researchers in those fields are particularly sensitive to the physical environment. They were able to identify four influential spatial characteristics: privacy, beauty, spatial diversity and proximity.…”
Section: Group 3: Studies Examining Specifically Designed Spaces For mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of innovative and creative ideas are closely related to investigation projects that have provided a solution to current problems for humanity. These solutions respond to new technological necessities, through feasible, viable innovative and creativity methods [4]. First of all, creativity can be directed to the generation of new and useful ideas, whereas innovation is regarded as the process of transforming the best ideas into real products.…”
Section: Introductionmentioning
confidence: 99%
“…Creativity with a focus on the environment, this axis as the most important factor is the formation of creative ideas. (Bisadi, Hosseini, 2012) in recent years in the field of creativity of children and students does a lot of research in the field of emotional-cognitive and educational issues. Unfortunately in the field of architecture and the role of architectural space less attention has been paid in nurturing creativity (Mahdavinezhad and Silvayeh, 2013).…”
Section: Introductionmentioning
confidence: 99%